The good master - Seredy, Kate.; Seredy, Kate. (New York : Scholastic Inc, 1991)
Two cousins spend an adventurous summer on a ranch on the Hungarian plains.
"A Newbery honor book--cover p. [4]
"A Puffin book, Ages 8-12"--cover p. [4]
Originally published: New York : Viking Press, 1935.
Keywords: Cousins -- Fiction; Hungary -- Fiction